2015
DOI: 10.1371/journal.pone.0138331
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Reference Genes for Gene Expression Normalization in Trichomonas vaginalis

Abstract: Trichomonas vaginalis is the etiologic agent of trichomonosis, the most common non-viral sexually transmitted disease worldwide. This infection is associated with several health consequences, including cervical and prostate cancers and HIV acquisition. Gene expression analysis has been facilitated because of available genome sequences and large-scale transcriptomes in T. vaginalis, particularly using quantitative real-time polymerase chain reaction (qRT-PCR), one of the most used methods for molecular studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 54 publications
3
12
0
Order By: Relevance
“…Using data from the exponential phase of the qPCR, threshold cycle base lines were set according to manufacturer protocols. Data from different samples were interpolated from standard curves established for each primer set and then normalized against the housekeeping alpha tubulin gene (dos Santos, de Vargas Rigo, Frasson, Macedo, & Tasca, ). The expression of housekeeping gene does not seem to change upon TSA treatment (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Using data from the exponential phase of the qPCR, threshold cycle base lines were set according to manufacturer protocols. Data from different samples were interpolated from standard curves established for each primer set and then normalized against the housekeeping alpha tubulin gene (dos Santos, de Vargas Rigo, Frasson, Macedo, & Tasca, ). The expression of housekeeping gene does not seem to change upon TSA treatment (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…To assess the expression levels of all 10 hydrogenase paralogs present in the T. vaginalis genome, we normalized their expression to the housekeeping gene of topoisomerase 2 43 (Figure S3). Four genes (TVAG_452140, TVAG_136330, TVAG_483690, and TVAG_447160) encode putatively cytosolic proteins (not found in the hydrogenosomal proteome 42 and without predicted organellar targeting peptide; Figure S2).…”
Section: Identification Of Hydrogenase In T Vaginalis Cytosolmentioning
confidence: 99%
“…The failure of amplification of the three housekeeping genes at all loci for all isolates may be due a problem in the sensitivity of the PCR or due to the nature of the genes being single-copy genes, although these genes were previously selected [28] based on being readily amplified and sequenced on both DNA strands of all T. vaginalis isolates. Dos Santos et al [49] found variable stability in the expression of nine housekeeping reference genes under different culture conditions. Genes encoding α-tubulin, actin and DNA TopII were the most stable and conversely, the widely used T. vaginalis reference genes encoding GAPDH and β-tubulin were less stable [49] .…”
Section: Discussionmentioning
confidence: 99%
“…Dos Santos et al [49] found variable stability in the expression of nine housekeeping reference genes under different culture conditions. Genes encoding α-tubulin, actin and DNA TopII were the most stable and conversely, the widely used T. vaginalis reference genes encoding GAPDH and β-tubulin were less stable [49] .…”
Section: Discussionmentioning
confidence: 99%